Influence of Parenting Styles on Adolescent Academic Achievement in Public Day Secondary Schools in Rachuonyo North Sub County, Kenya. - Odongo, Alice A. (JOOUST, 2016)
There has been continued relatively low academic performance among secondary school students in Rachuonyo North Sub-County. Previous studies indicate that performance could be attributed to adequate school resources, teacher factors and student personal factors. However, - ere is scanty literature on the influence of parenting style on the academic achievement among secondary students in Rachuonyo North Sub-County. The present study sought to establish the • influence of parenting styles on adolescent academic achievement in day secondary schools in North Rachuonyo Sub-County, Homa Bay County, Kenya. The study objectives were: To find out the influence of authoritarian parenting style on adolescent academic achievement; to establish the influence of authoritarian parenting type on adolescent academic achievement; to examine the influence of permissive parenting type on adolescent academic achievement and to determine the influence of neglectful parenting type on adolescent academic achievement. 3aurnrind's theory of parenting style informed the study. The Concurrent Triangulation Design 11s used. The target population comprised 2409 day secondary students registered for KCSE in _015 in 47 schools in Rachuonyo orth Sub-County. The sample size comprised 263 secondary school students drawn from Sub-County day secondary schools. Ten Principals were randomly selected for interviews. Baurnrind's parenting styles questionnaire and interview schedule were used to collect the data from the students and principals respectively. Validity of the questionnaire was ensured by expertise judgment from university lecturers while reliability was =-e ermined by internal consistency and reliability coefficient of 0.718 was reported. Quantitative data was analysed using Pearson Correlation while qualitative data was analysed using Thematic analysis. The study found out a strong positive influence (r = 0.786) of authoritative parenting style on academic achievement; there was a strong negative influence of r = -0.618 of authoritative parenting style on academic achievement. There was an average negative influence _: r=-0.477 of permissive parenting style on academic achievement, and finally a significant Influence of r=-0.796 of neglectful parenting style on academic achievement of students in day =- secondary schools. The study recommended that teacher counselors should identify at risk __ dents from the parents susceptible of negative influence and offer appropriate therapy.
Keywords: Parenting Styles.; Parenting Styles on Adolescents.; Academic Achievement in Public Day Secondary Schools.; Kenya.